The great Buster [videorecording (DVD)] : a celebration - Bogdanovich, Peter, 1939-; Bogdanovich, Peter, 1939-; Tarantino, Quentin; Brooks, Mel, 1926-; Reiner, Carl, 1922-2020- (Contemporary classics (Cohen Media Group)., 2019)
The film celebrates the life and career of one of America's most influential and celebrated filmmakers and comedians, Buster Keaton, whose singular style and fertile output during the silent era created his legacy as a true cinematic visionary. Filled with stunningly restored archival Keaton films from the Cohen Film Classics library, it is directed by Peter Bogdanovich, a filmmaker and cinema historian.